Analysis of anatomical variants of frontal sinus outflow tract (FSOT) by multiplanar reconstruction MDCT scan images - Mohamed, Ahmad Firdaus (2020)
Introduction:The frontal sinus has the most complex and variable drainage of any paranasal sinus. Its outflow tract and anatomical structure is critical for safe endoscopic navigation during functional endoscopic sinus surgery. It includes the frontal infundibulum, ostium and recess in the direction of the drained secretion. The actual course may vary depending on pneumatization pattern of surrounding bones. The agger nasi cell (ANC) as most commonly found in population plays crucial role as anatomical landmark for the recess. Its volume is related to frontal beak (FB) thickness, frontal isthmus (FI) and frontal recess (FR) length. The purpose of this study is to determine correlation of ANC volume with the FB thickness, FI and FR length in adult patient in Hospital Universiti Sains Malaysia (HUSM), based on the fact that there is significant correlation of volume of ANC with the FB thickness, FI and FR length. Methodology: A cross sectional study was conducted in 140 adult patients aged above 18 years old with no previous history of paranasal sinuses surgery who had CT Brain done in HUSMfrom January 2010 to June 2018. 3- dimensional (3D) images were constructed using Multiplanar Reconstructed (MPR) technique from thin-sliced (1mm) image of CT brain. The coronal and parasaggital view clearly showed frontal sinus cells, pneumatisation pattern, location and variants. The measurement of Agger Nasi cell volume, frontal beak thickness, frontal recess and frontal isthmus length were performed using facial bone review of high kernel algorithm. Correlation between volume of agger nasi cell with frontal beak thickness, A-P length of frontal isthmus and frontal recess determined using Pearson correlation test. Results: ANC found in 131 out of 140 adult patients (93.6%). Mean ANC volume 434.48 with standard deviation of 256.63. For FB thickness, A-P length of FI & FR, mean are 6.24 (SD 1.61) mm, 7.06 (SD 2.92) mm and 4.95 (SD 2.97) mm respectively. No significant correlation found between volume of ANC with FB thickness, A-P length of FI and FR. Conclusion: Thickness of FB did not correlate with volume of ANC and no significant correlation with A-P length of FI & FR with volume of ANC.